Two-component mortar system based on aluminous cement and calcium silicate and its use
By using component A of the barrier agent and component B of the barrier cement in the two-component aqueous glue system, the existing glue system has been solved, and the stable storage, environmental protection, safe operation and good performance in high temperature and humidity environments of the glue system are achieved.
Patent Information
- Application Number
- JP2024551666
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-08
- Filing Date
- 2023-02-28
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-02-28
AI Technical Summary
The existing two-component water-based glue system has problems such as poor stability, high toxicity, environmental pollution, inconvenient operation and reduced performance in high temperature and humidity environments during storage and use.
A two-component aqueous glue system containing aqueous Yar titanate cement component A and blocking calcium silicate cement component B is adopted, wherein component A contains a barrier such as phosphoric acid, boric acid, etc., and component B contains a barrier calcium silicate cement and water, and stimulates the solidification process by mixing each other.
It realizes stable storage, environmental protection, safe operation of the glue system, maintains good mechanical properties in high temperature and humidity environments, and reduces the use ratio of cement and silicate, thereby improving long-term performance.
Smart Images

Figure 2025509147000001 
Figure 2025509147000002 
Figure 2025509147000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a two-component mortar system for the chemical fixation of anchoring means in mineral substrates, comprising a cured aqueous phase aluminous cement component A and an initiator component B in the aqueous phase for starting the curing process, component A further comprising at least one blocking agent selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid and phosphonic acid, and water, and component B comprising a blocked calcium silicate cement and water.Furthermore, the present invention relates to a ready-to-use two-component mortar system for the chemical fixation of anchoring means, preferably metal elements, in mineral substrates such as brickwork, concrete, permeable concrete or structures made of natural stone, as well as to the use thereof for the chemical fixation of anchoring means. [Background technology]
[0002] There are many two-component mortar systems, sometimes referred to as kit-of-parts, in which the components are mixed before use or during application to start the curing process and are intended to provide good chemical fixation of the anchoring means in the mineral matrix. For example, when fast hardening is desired, organic systems based on free radical polymerizable resins are used. However, such systems are generally known to be polluting, expensive, potentially dangerous and / or toxic for the environment and for the people who handle them, and they often need to be specially labeled. Moreover, organic systems often show a significant decrease in stability when exposed to strong sunlight or otherwise thermally at high temperatures, thereby reducing their mechanical performance with respect to the chemical fixation of the anchoring means.
[0003] To overcome these shortcomings, mainly mineral systems based on alumina cement have been developed. Alumina cement has monocalcium aluminate as its main component and is widely used in the building and construction industry because the final product shows a high level of mechanical performance over time. Alumina cement is also resistant to bases, achieves maximum strength more quickly than Portland cement, and can withstand solutions of sulfates. Therefore, alumina cement systems are preferably used in the field of chemical fixation.
[0004] Furthermore, calcium aluminate slurries are known to provide high fire resistance at anchorage points. However, compared to resin-based anchoring mortars, the setting of such systems is rather slow, which requires longer waiting times on site and often interrupts the workflow. This is especially important for anchoring applications where immediate loading is crucial. In addition, calcium aluminate-based mortars are characterized by the presence of the metastable hydrate phase CAH 10 and C2AH8 to the stable hydrate C3AH6, undergoing conversion resulting in reduced performance over time. This is particularly evident in warm and humid environments where established metastable cement hydrates convert to a denser state, increasing porosity and ultimately reducing performance.
[0005] Blends of powdered ordinary Portland cement with calcium aluminate or calcium sulfoaluminate cements are known for the development of rapid repair mortars. Since calcium aluminate cements are much more reactive than ordinary Portland cements, their addition in small amounts of about 10% of the total cement content allows for shorter curing times and higher early age strength, e.g., less than one day. However, commercial products for rapid repair, such as Fastset repair mortars by Quikrete®, required on-site preparation by mixing powdered cement with a liquid phase.
[0006] In EP 2 162 410 a two-component system is described, which comprises a part A based on an aqueous phase alumina cement retarded by boric acid or its salts, and a part B for initiating the curing process. The initiator in part B is made only of lithium salts. In EP 0 081 385 a two-component system is also disclosed, which comprises an aqueous high alumina cement composition with inhibited setting and a reactivator composition containing lithium salts. In EP 2 794 510 a stabilized aqueous suspension is described, which comprises an alumina cement and / or calcium sulfoaluminate cement, which is inhibited by phosphorus-containing compounds and can be stored for a sufficient time even at high temperatures. The stabilized aqueous suspension can serve as a base for surface coatings.
[0007] However, these aqueous alumina cement suspensions retarded by boric acid or its salts are often not very stable for a sufficient period of time for storage before use. Moreover, boric acid is highly toxic and ecotoxic. Furthermore, these state-of-the-art systems require high water-to-cement ratios and are characterized by their undesirable conversion, which reduces their performance over time.
[0008] German Patent No. 2311239 describes an adjuvant composition for improving the setting and hardening properties of alumina cements and mortars, comprising lithia, a water-soluble lithium salt, and a hydroxylated organic acid or its salt or ester. The fluid may be directly incorporated into the alumina cement or into the mortar and concrete during their manufacture or added to the mixing water during application. However, a drawback of this system is that the cement composition and the activator composition cannot be stored for a sufficient time to be ready for use, and therefore must be freshly prepared before use depending on the desired setting and hardening time, resulting in more procedural steps before application. Also, the lithium-based activator component is expensive and its extraction is problematic from a humanitarian, economic and political point of view.
[0009] Therefore, there is a need for a ready-to-use multi-component system, preferably a two-component system, which is superior to the systems of the prior art in terms of environmental aspects, health and safety, handling, storage time, sustainability, and a good balance between setting and hardening of the mortar.Furthermore, it is of interest to provide a system that can be used for chemical fixing of anchoring means in mineral substrates without adversely affecting the handling, properties and mechanical performance of the chemical anchoring system, as well as to provide a system that uses a lower water-to-cement ratio and conversion, which increases the performance over time.
[0010] In view of the above, it is an object of the present invention to provide a multi-component system, in particular a two-component mortar system, which overcomes the drawbacks of the systems of the prior art, in particular a two-component mortar system, which is ready to use, easy to handle, environmentally friendly, can be stably stored for a certain period of time before use, presents a good balance between setting and hardening, still has good mechanical performance with regard to chemical fixing of the anchoring means even under the effect of elevated temperatures, and is further characterized by the ability to reduce the water-to-cement ratio and conversion.
[0011] It is further an object of the present invention to provide a two-component mortar system which can be used for the chemical fixation of, preferably metal elements of, an anchoring means in mineral substrates such as brickwork, concrete, permeable concrete or structures made of natural stone, as well as to provide a method for fixing said anchoring means.
[0012] These and other objects which will become apparent from the ensuing description of the invention are solved by the invention as set forth in the independent claims. The dependent claims relate to preferred embodiments.
[0013] Summary of the Invention In one aspect, the present invention provides a ready-to-use two-component mortar system comprising a cured aqueous phase aluminous cement component A and an initiator component B in the aqueous phase to start the curing process, component A further comprising at least one blocking agent selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid and phosphonic acid, and water, and component B comprising a blocked calcium silicate cement and water. In particular, component B comprises the siliceous clinker phase tricalcium silicate C3S, dicalcium silicate C2S, or mixtures thereof, and a blocking agent selected from the group consisting of monosaccharides, carboxylic acids, gluconic acid, glycolic acid, lignosulfonates, phosphoric and phosphonic acids, their salts and esters, glucose, and mixtures thereof.
[0014] In another aspect, the present invention provides a two-component mortar system used for the chemical fixation of anchoring means, preferably of metal elements, in mineral substrates such as brickwork, concrete, permeable concrete or structures made of natural stone, and in another aspect a method for fixing said anchoring means and a method for fixing said anchoring means. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The following terms and definitions are used in the context of the present invention.
[0016] As used in the context of the present invention, the singular forms "a" and "an" also include the respective plural forms unless the context clearly dictates otherwise. Thus, the terms "a" or "an" are intended to mean "one or more" or "at least one," unless otherwise specified.
[0017] The term "aluminous cement" in the context of the present invention refers to calcium aluminate cement, consisting mainly of hydrated active calcium aluminate. Another name is "high aluminous cement" or "Ciment fondu" in French. The main active ingredient of calcium aluminate cement is monocalcium aluminate (CaAl2O4, CaO·Al2O3, or CA in cement chemical notation).
[0018] The term "siliceous clinker phase" refers to the clinker phases of ordinary Portland cement clinker, tricalcium silicate C3S or dicalcium silicate C2S, or mixtures thereof, and thus the siliceous clinker phase is essentially free of aluminate clinker phases and is free of lime.
[0019] The term "initiator" in the context of the present invention refers to a compound or composition that modifies the chemical environment to initiate a specific chemical reaction. In the present invention, the initiator modifies the pH value of the mortar suspension, thereby deblocking the hydraulic binder in the final mix.
[0020] The term "binder" or "binder component" in the context of the present invention refers to the calcium-aluminate based cementitious component and other additional optional components such as, for example, fillers. In particular, the term "main binder component" refers to component A.
[0021] The term "water to cement ratio" in the context of the present invention refers to the ratio of (water) to (calcium aluminate cement and siliceous clinker phases), i.e. water / CAC+C2S, or water / CAC+C3S, or water / CAC+C2S+C3S.
[0022] Surprisingly, the inventors have found that the two-component mortar system according to the invention is an easy-to-handle ready-to-use system for chemically fixing anchoring means in mineral substrates.In particular, it has been found that an aqueous slurry-based system containing a blocked alumina component as the main binder component and a blocked calcium silicate cement in an aqueous slurry with an alkaline pH as the second binder component can use a lower water-to-cement ratio compared to state-of-the-art two-component injection mortars containing a filler-based activator component.In addition, it has been found that the long-term strength loss due to conversion characteristic of calcium aluminate cement can be mitigated by blending these two cements to produce stable calcium silicate hydrate and portlandite hydrate phases.
[0023] While typical calcium aluminate-based binders rely on synthetic or mined carbonate sources to mitigate strength loss due to conversion phenomena, calcium silicate cement can be used as a binder. By blocking calcium silicate cement with sugars, such as gluconate, in water, an alkaline pH is achieved that can be used to activate the blocked calcium aluminate cement components. Thus, a separate activator such as sodium hydroxide or lithium hydroxide is not required. The alkaline pH generated from the hydration of calcium aluminate cement subsequently activates the calcium silicate cement.
[0024] Furthermore, it has been found that the two-component mortar system of the present invention does not contain any harmful substances while maintaining the standards for chemical bonding applications, and therefore also encompasses reduced labeling.
[0025] The present invention relates to a two-component mortar system for chemically fixing anchoring means in mineral substrates, comprising a cured aqueous phase aluminous cement component A and an initiator component B in the aqueous phase for starting the curing process. In particular, component A further comprises at least one blocking agent selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid and phosphonic acid, and water, and component B comprises a blocked calcium silicate cement and water.
[0026] Component A according to the invention is based on aqueous calcium aluminate cement (CAC) or aqueous calcium sulfoaluminate cement (CAS). Calcium aluminate cements that can be used in the invention are characterized by rapid setting and hardening, rapid drying and shrinkage compensation when mixed with calcium sulfate, good corrosion and shrinkage resistance. Such calcium aluminate cements suitable for use in the invention are, for example, Ternal® White (Kerneos, France).
[0027] When component A contains a mixture of calcium aluminate cement (CAC) and calcium sulfate (CaSO4), rapid ettringite formation occurs during hydration. In concrete chemistry, the reaction of calcium aluminate with calcium sulfate leads to the formation of hexacalcium aluminate trisulfate hydrate, represented by the general formula (CaO)6(Al2O3)(SO3)3·32H2O or (CaO)3(Al2O3)(CaSO4)3·32H2O, resulting in rapid setting and hardening as well as shrinkage compensation or even expansion. Shrinkage compensation can be achieved by moderately increasing the sulfate content.
[0028] Component A of the present invention comprises at least about 40% by weight, preferably at least about 50% by weight, more preferably at least about 60% by weight, and most preferably at least about 70% by weight, about 40% to about 95% by weight, preferably about 50% to about 90% by weight, more preferably about 60% to about 85% by weight, and most preferably about 70% to about 80% by weight of calcium aluminate cement, based on the total weight of component A.
[0029] According to an alternative embodiment of the present invention, component A comprises at least about 20% by weight, preferably at least about 30% by weight, more preferably at least about 40% by weight, most preferably at least about 50% by weight, about 20% to about 80% by weight, preferably about 30% to about 70% by weight, more preferably about 35% to about 60% by weight, most preferably about 40% to about 55% by weight of alumina cement, based on the total weight of component A, and at least about 5% by weight, preferably at least about 10% by weight, more preferably at least about 15% by weight, most preferably at least about 20% by weight, about 1% to about 50% by weight, preferably about 5% to about 40% by weight, more preferably about 10% to about 30% by weight, most preferably about 15% to about 25% by weight of calcium sulfate, preferably calcium sulfate hemihydrate, based on the total weight of component A. In a preferred alternative embodiment of the two-component mortar system of the present invention, the ratio of CaSO4 / CAC in component A should be 35:65 or less.
[0030] The blocking agent contained in component A according to the present invention is selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid, and phosphonic acid, preferably phosphoric acid or metaphosphoric acid, and most preferably phosphoric acid, in particular an 85% aqueous solution of phosphoric acid. Component A contains at least about 0.1% by weight, preferably at least about 0.3% by weight, more preferably at least about 0.4% by weight, most preferably at least about 0.5% by weight, about 0.1% to about 20% by weight, preferably about 0.1% to about 15% by weight, more preferably about 0.1% to about 10% by weight, most preferably about 0.3% to about 10% by weight of the blocking agent, based on the total weight of component A. In a preferred embodiment, component A contains about 0.3% to about 10% by weight of an 85% aqueous solution of phosphoric acid, based on the total weight of component A.
[0031] In advantageous embodiments, component A further comprises the following properties, either alone or in combination:
[0032] Component A may additionally comprise a plasticizer. The plasticizer may be selected from the group consisting of low molecular weight (LMW) polyacrylic acid polymers, superplasticizers from the family of polyphosphonate polyox and polycarbonate polyox, and Ethacryl superplasticizers from the polycarboxylate ether group, and mixtures thereof, such as Ethacryl™ G (Coatex, Arkema Group, France), Acumer™ 1051 (Rohm and Haas, UK), or Sika® ViscoCrete®-20 HE (Sika, Germany). Suitable plasticizers are commercially available products. Component A may contain at least about 0.2% by weight, preferably at least about 0.3% by weight, more preferably at least about 0.4% by weight, and most preferably at least about 0.5% by weight, about 0.2% to about 20% by weight, preferably about 0.3% to about 15% by weight, more preferably about 0.4% to about 10% by weight, and most preferably about 0.5% to about 5% by weight of the plasticizer, based on the total weight of component A.
[0033] Component A may additionally comprise a thickening agent. Thickening agents that may be used in the present invention may be selected from the group consisting of organic products such as xanthan gum, welan gum or DIUTAN® gum (CP Kelko, USA), mineral products such as starch-derived ethers, guar-derived ethers, polyacrylamides, carrageenan, agar, and clay, and mixtures thereof. Suitable thickening agents are commercially available products. Component A comprises at least about 0.01% by weight, preferably at least about 0.1% by weight, more preferably at least about 0.2% by weight, most preferably at least about 0.3% by weight, about 0.01% to about 10% by weight, preferably about 0.1% to about 5% by weight, more preferably about 0.2% to about 1% by weight, most preferably about 0.3% to about 0.7% by weight of said thickening agent, based on the total weight of component A.
[0034] Component A may further comprise an antibacterial agent or biocide. The antibacterial agent or biocide that may be used in the present invention may be selected from the group consisting of compounds of the isothiazolinone family, such as methylisothiazolinone (MIT), octylisothiazolinone (OIT), and benzoisothiazolinone (BIT), and mixtures thereof. Suitable antibacterial agents or biocides are commercially available products. Ecocide K35R (Progiven, France) and Nuosept OB 03 (Ashland, The Netherlands) are mentioned by way of example. Component A comprises at least about 0.001% by weight, preferably at least about 0.005% by weight, more preferably at least about 0.01% by weight, and most preferably at least about 0.015% by weight, from about 0.001% to about 1.5% by weight, preferably from about 0.005% to about 0.1% by weight, more preferably from about 0.01% to about 0.075% by weight, and most preferably from about 0.015% to about 0.03% by weight of said antimicrobial or biocide, based on the total weight of Component A. In a preferred embodiment, Component A comprises from about 0.015% to about 0.03% by weight of Nuosept OB 03, based on the total weight of Component A.
[0035] Component A may further comprise at least one mineral filler. The mineral filler that may be used in the present invention may be limestone filler, such as calcite, sand, corundum, dolomite, alkali-resistant glass, crushed stone, gravel, gravel, quartz, quartz flour, quartz sand, clay, fly ash, fumed silica, brick powder, rice peel ash, phonolite, calcined clay and metakaolin, carbonate compounds, pigments, titanium dioxide, lightweight fillers, or mixtures thereof. Suitable fillers are commercially available products. Component A may comprise at least about 1% by weight, preferably at least about 2% by weight, more preferably at least about 5% by weight, and most preferably at least about 8% by weight of the at least one filler, based on the total weight of component A.
[0036] The water content in component A is at least about 1% by weight, preferably at least about 5% by weight, more preferably at least about 10% by weight, and most preferably at least about 20% by weight, from about 1% by weight to about 50% by weight, preferably from about 5% by weight to about 40% by weight, more preferably from about 10% by weight to about 30% by weight, and most preferably from about 15% by weight to about 25% by weight, based on the total weight of component A.
[0037] The presence of plasticizers, thickeners, antimicrobials, biocides, or fillers does not change the overall inorganic nature of the cementitious component A.
[0038] Component A, which comprises a calcium aluminate or calcium sulfoaluminate cement, is present in the aqueous phase, preferably in the form of a slurry or paste.
[0039] The initiator component B of the present invention comprises a blocked calcium silicate cement and water.
[0040] The blocked calcium silicate cement of component B comprises a calcium silicate cement and a blocking agent.
[0041] In particular, the blocked calcium silicate cement comprises the siliceous clinker phase tricalcium silicate C3S, dicalcium silicate C2S or a mixture thereof, preferably the blocked calcium silicate cement is tricalcium silicate C3S or dicalcium silicate C2S. In the most preferred embodiment, the calcium silicate cement is aluminate clinker phase-free and lime-free tricalcium silicate C3S or dicalcium silicate C2S, most preferably aluminate clinker phase-free and lime-free tricalcium silicate C3S.
[0042] Component B of the present invention comprises at least about 5% by weight, preferably at least about 10% by weight, more preferably at least about 20% by weight, and most preferably at least about 30% by weight, about 5% to about 95% by weight, preferably about 10% to about 90% by weight, more preferably about 20% to about 80% by weight, and most preferably about 30% to about 75% by weight of calcium silicate cement, based on the total weight of component B.
[0043] The blocking agent for calcium silicate cement is selected from the group consisting of monosaccharides, carboxylic acids, gluconic acid, glycolic acid, lignosulfonates, phosphoric and phosphonic acids, their salts and esters, glucose, and mixtures thereof, preferably glucose or sodium gluconate, most preferably sodium gluconate.
[0044] Component B contains at least about 0.01% by weight, preferably at least about 0.05% by weight, more preferably at least about 0.1% by weight, and most preferably at least about 1.0% by weight, about 0.01% to about 25% by weight, preferably about 0.05% to about 20% by weight, more preferably about 0.1% to about 15% by weight, and most preferably about 1.0% to about 10% by weight of the blocking agent, based on the total weight of component B. In a most preferred embodiment, component B contains about 0.01 to about 0.4% by weight of sodium gluconate, based on the total weight of component B.
[0045] The ratio of blocking agent:C3S is preferably 1:300, more preferably 1:500, and most preferably 1:1000.
[0046] The water content in component B is at least about 1% by weight, preferably at least about 5% by weight, more preferably at least about 10% by weight, and most preferably at least about 20% by weight, from about 1% by weight to about 60% by weight, preferably from about 5% by weight to about 50% by weight, more preferably from about 10% by weight to about 40% by weight, and most preferably from about 15% by weight to about 30% by weight, based on the total weight of component B.
[0047] In advantageous embodiments, component B further comprises the following properties, alone or in combination:
[0048] Component B may additionally comprise a thickener. The thickener used in the present invention may be selected from the group consisting of bentonite, silicon dioxide, quartz, acrylate-based thickeners such as alkali-soluble or alkali-swellable emulsions, fumed silica, clays, and titanate chelating agents. Mention may be made by way of example of polyvinyl alcohol (PVA), hydrophobically modified alkali soluble emulsion (HASE), hydrophobically modified ethylene oxide urethane polymers known in the art as HEUR, and cellulosic thickeners such as hydroxymethyl cellulose (HMC), hydroxyethyl cellulose (HEC), hydrophobically-modified hydroxy ethyl cellulose (HMHEC), sodium carboxymethyl cellulose (SCMC), sodium carboxymethyl 2-hydroxyethyl cellulose, 2-hydroxypropyl methylcellulose, 2-hydroxyethyl methylcellulose, 2-hydroxybutyl methylcellulose, 2-hydroxyethyl ethylcellulose, 2-hydroxypropyl cellulose, attapulgite clays, and mixtures thereof. Suitable thickeners are commercially available products such as Optigel WX (BYK-Chemie GmbH, Germany), Rheolate 1 (Elementis GmbH, Germany), and Cellosize™, Acrysol ASE-60 (The Dow Chemical Company).Component B contains at least about 0.01 wt. %, preferably at least about 0.05 wt. %, more preferably at least about 0.1 wt. %, and most preferably at least about 0.3 wt. %, from about 0.01 wt. % to about 15 wt. %, preferably from about 0.05 wt. % to about 10 wt. %, more preferably from about 0.1 wt. % to about 5 wt. %, and most preferably from about 0.1 wt. % to about 1 wt. % of the thickener, based on the total weight of component B.
[0049] Component B may additionally comprise a plasticizer. The plasticizer may be selected from the group consisting of low molecular weight (LMW) polyacrylic acid polymers, superplasticizers from the family of polyphosphonate polyox and polycarbonate polyox, and Ethacryl superplasticizers from the polycarboxylate ether group, and mixtures thereof, such as Ethacryl™ G (Coatex, Arkema Group, France), Acumer™ 1051 (Rohm and Haas, UK), or Sika® ViscoCrete®-20 HE (Sika, Germany). Suitable plasticizers are commercially available products. Component B may contain at least about 0.2 wt %, preferably at least about 0.3 wt %, more preferably at least about 0.4 wt %, and most preferably at least about 0.5 wt %, of the plasticizer in an amount of about 0.2 wt % to about 20 wt %, preferably about 0.3 wt % to about 15 wt %, more preferably about 0.4 wt % to about 10 wt %, and most preferably about 0.5 wt % to about 5 wt %, based on the total weight of component B.
[0050] Component B may optionally comprise at least one mineral filler. The mineral filler that may be used in the present invention may be limestone filler, such as calcite, sand, corundum, dolomite, alkali-resistant glass, crushed stone, gravel, gravel, quartz, quartz flour, quartz sand, clay, fly ash, fumed silica, brick powder, rice husk ash, phonolite, calcined clay and metakaolin, carbonate compounds, pigments, titanium dioxide, lightweight fillers, or mixtures thereof. Suitable fillers are commercially available products. Component B may comprise at least about 1% by weight, preferably at least about 10% by weight, more preferably at least about 20% by weight, and most preferably at least about 30% by weight of said at least one filler, based on the total weight of component B. The at least one mineral filler contained in component B according to the present invention is preferably a mixture of mineral fillers. The at least one mineral filler is selected to obtain a particle size complementary to the aluminous cement and the calcium silicate cement.
[0051] The presence of plasticizers and thickeners does not change the overall inorganic character of Component B.
[0052] Component B, which comprises the blocked calcium silicate cement, is present in the aqueous phase, preferably in the form of a slurry or paste.
[0053] Furthermore, component A and / or component B may contain an accelerator component. The accelerator component is composed of at least one alkali and / or alkaline earth metal salt selected from the group consisting of hydroxides, chlorides, sulfates, phosphates, monohydrogen phosphates, dihydrogen phosphates, nitrates, carbonates, and mixtures thereof, preferably the accelerator component is an alkali or alkaline earth metal salt, more preferably a water-soluble alkali or alkaline earth metal salt, more preferably a calcium metal salt such as calcium hydroxide, calcium sulfate, calcium carbonate, calcium chloride, calcium formate, or calcium phosphate, a sodium metal salt such as sodium hydroxide, sodium sulfate, sodium carbonate, sodium chloride, sodium formate, or sodium phosphate, or a lithium metal salt such as lithium hydroxide, lithium sulfate, lithium sulfate monohydrate, lithium carbonate, lithium chloride, lithium formate, or lithium phosphate, and most preferably lithium sulfate or lithium sulfate monohydrate. Components A and / or B contain at least about 0.01% by weight, preferably at least about 0.05% by weight, more preferably at least about 0.1% by weight, and most preferably at least about 1.0% by weight, of the accelerator in an amount of from about 0.01% to about 25% by weight, preferably from about 0.05% to about 20% by weight, more preferably from about 0.1% to about 15% by weight, and most preferably from about 1.0% to about 10% by weight, based on the total weight of components A or B, respectively.
[0054] It is preferred that the pH value of component B is greater than 10, more preferably greater than 11, most preferably greater than 12, in particular in the range 10-14, preferably in the range 11-13.
[0055] In the most preferred embodiment, component A comprises or consists of the following components: 70-80% by weight calcium aluminate cement, 0.5 to 1.5% by weight of phosphoric acid, 0.5 to 1.5% by weight of a thickening agent, 0.5 to 1.5% by weight of a plasticizer, 0.001 to 0.05% by weight of an antimicrobial or biocide, 15-25% water by weight.
[0056] In the most preferred embodiment, component B comprises or consists of the following components: 45% to 85% by weight of calcium silicate cement, 0.01 to 0.5% by weight of sodium gluconate, and 10% to 35% water by weight.
[0057] In the most preferred embodiment, component B comprises or consists of the following components: 45% to 85% by weight of C3S, which is free of aluminate clinker phase and free of lime, 0.01 to 0.5% by weight of sodium gluconate, and 10% to 35% water by weight.
[0058] Component A of the present invention can be prepared as follows: A phosphorus-containing blocking agent is mixed with water such that the pH value of the resulting mixture is about 2. A plasticizer is added and the mixture is homogenized. Alumina cement, optionally calcium sulfate, and optionally mineral filler are premixed and gradually added to the mixture with increasing stirring speed such that the pH value of the resulting mixture is about 4. Finally, the thickener and antimicrobial / biocide, and optionally accelerator components are added and mixed until the mixture is completely homogenous.
[0059] Component B of the present invention can be prepared as follows: calcium silicate cement and blocking agent are mixed with water until the mixture is homogeneous.Finally, optional fillers, thickeners and plasticizers, and accelerator components can be added until the mixture is completely homogeneous.
[0060] Components A and B are present in the aqueous phase, preferably in the form of a slurry or paste. In particular, components A and B have a pasty to fluidic appearance according to their respective compositions. In a preferred embodiment, components A and B are in the form of a paste, thereby preventing sagging when mixing the two components.
[0061] The weight ratio between component A and component B (A / B) is preferentially comprised between 7 / 1 and 1 / 3, preferably 3 / 1. Preferably, the composition of the mixture comprises 75% by weight of component A and 25% by weight of component B. In an alternative embodiment, the composition of the mixture comprises 25% by weight of component A and 75% by weight of component B.
[0062] The present two-component system is mineral in nature and is not affected by the presence of additional thickening agents or other agents.
[0063] The shelf life of the two-component system depends on the individual shelf life of each of the respective components, in particular components A and B, which have a shelf life of at least 6 months at ambient temperature to protect the system from storage and delivery delays. Most preferably, components A and B are individually stable for at least 6 months. Components A and B were stored in closed containers at 20°C to avoid water evaporation and were checked for flowability, homogeneity, whether sedimentation occurs, and any changes in pH value after several time intervals. The properties of all components remained unaffected after 6 months, so the shelf life is at least 6 months at 20°C.
[0064] After mixing of the two components A and B, it is preferred that the two-component mortar system has an initial setting time of at least 5 minutes, preferably at least 10 minutes, more preferably at least 15 minutes, most preferably at least 20 minutes, in particular in the range of about 5 to 25 minutes, preferably in the range of about 10 to 20 minutes.
[0065] In multi-component mortar systems, especially two-component mortar systems, the volume ratio of cementitious component A to initiator component B is between 1:1 and 7:1, preferably 3:1. In an alternative embodiment, the volume ratio of cementitious component A to initiator component B is between 1:3 and 1:2.
[0066] After being produced separately, components A and B are introduced into separate containers, from which they are discharged by a mechanical device and led through a mixing device. The two-component mortar system of the invention is preferably a ready-to-use system, in which components A and B are placed separately from each other in a multi-chamber device, such as a multi-chamber cartridge and / or a multi-chamber cylinder, or in a two-component capsule, preferably in a two-chamber cartridge or a two-component capsule. The multi-chamber system preferably comprises two or more foil bags for separating the cured component A and the initiator component B. The contents of the chambers or bags, which are mixed together by the mixing device, preferably via a static mixer, can be injected into the borehole. It is also possible to assemble in a set of multiple chamber cartridges or pails or buckets.
[0067] The settable alumina cement composition leaving the static mixer is inserted directly into the borehole where it is needed for fixing the anchoring means and where the mineral matrix is first introduced during the chemical fixing of the anchoring means, after which the construction elements to be fixed, such as anchor rods, are inserted and adjusted, after which the mortar composition sets and hardens. In particular, the two-component system of the present invention is considered as a chemical anchor for fixing anchoring means, in particular metal elements.
[0068] The two-component mortar system of the present invention can be used for the chemical fixing of fastening means, preferably metal elements such as anchor rods, especially threaded rods, bolts, steel reinforcements, in mineral substrates such as brickwork, concrete, permeable concrete or structures made of natural stone. In particular, the two-component mortar system of the present invention can be used for the chemical fixing of fastening means, such as metal elements in boreholes. It can be used for fastening purposes that include increased load capacity at temperatures above room temperature or at elevated temperatures, for example above 80° C., and / or increased bond strength stresses in the cured state.
[0069] In particular, the two-component mortar system of the invention is used in a method for chemically fixing an anchoring means in a mineral substrate, comprising the steps of introducing a borehole into the mineral substrate, mixing component A with component B to obtain a settable alumina cement composition, inserting this alumina cement composition directly into the borehole, inserting and adjusting the construction element to be fixed, and allowing the alumina cement composition to harden and set.
[0070] Furthermore, the two-component mortar system of the present invention may be used for coating or for attaching fibers, scrims, fabrics or composites, in particular high modulus fibers, preferably carbon fibers, in particular for the reinforcement of building structures, for example walls or ceilings or floors, or even for placing components, such as plates or blocks made of stone, glass or plastic, on buildings or construction elements.
[0071] The following examples illustrate the invention without, however, limiting it thereto. EXAMPLES
[0072] 1. Preparation of Components A and B First, the cementitious component A and the initiator component B are prepared by mixing the components specified in Tables 1 and 2, respectively. The percentages given are expressed in weight percent.
[0073] Specifically, 19.86 grams of deionized water, 0.75 grams of 85% phosphoric acid (blocking agent), 0.6 grams of Ethacryl G (superplasticizer), and 0.015 grams of Nuosept® (biocide) were homogenized at room temperature, and calcium aluminate cement (78.28 grams, pure Ternal White®) was added in small portions one after another while stirring with a dissolver, finally obtaining a smooth liquid paste-like slurry of blocked cement in water with a pH of less than 7. After the calcium aluminate cement was added, 0.5 grams of xanthan gum (thickener) was added, and the slurry was homogenized at 2000 rpm for 5 minutes.
[0074] [Table 1]
[0075] An exemplary preparation of component B is as follows: Tricalcium silicate (C3S), water, and sodium gluconate were mixed and homogenized. The pH of the blocked silicate slurry was about 12.
[0076] [Table 2]
[0077] 2. Calorimetric Observation Mixtures of silicate and aluminate mortars were prepared with varying C3S / CA ratios according to Table 3. Extra water was added to fix the water / (C3S+CA) ratio at 0.4, and the mortars were mechanically mixed in a high-speed mixer. The details of the mixtures, the weight ratios of the two slurries A:B, and their overall C3S:CAC ratios are given in Table 3.
[0078] [Table 3]
[0079] The possibility of reactivating the cement binder by combining the two blocked systems is measured by the heat output of hydration. The dissolution of the clinker phase is exothermic and measuring the heat output is favorable to follow the hydration. All the masses were hard by the end of the test (7 days), indicating that they can be used for fixing of anchoring means. The heat outputs are summarized in Table 4.
[0080] [Table 4]
[0081] Table 4 shows the effect of the blocking agent (sodium gluconate) dosage on the total heat output of the C3S-rich blends. Comparing Example 3 with Example 5 and Example 4 with Example 6 for a fixed C3S / CAC ratio, it can already be seen that increasing the amount of blocking agent reduces the heat output by the seventh day of hydration, meaning that less reactions have occurred during that period, lowering the loading values at early ages. Comparing Example 3 with Example 4 and Example 5 with Example 6 for a fixed blocking agent / C3S ratio, increasing the C3S fraction in the system reduces the heat output of the mortar. However, the heat increases and the mass hardens.
[0082] The heat output of mortars with blends varying the C3S to CAC ratio, varying the C3S in the blends from 85% to 15%, is also shown in Table 4. For blends containing 85% C3S, the lowest heat output was recorded by day 7. When the C3S fraction was replaced by calcium aluminate fraction, the heat output increased continuously by day 7.
[0083] As shown above, the two-component mortar system of the present invention offers a curing rate and mechanical strength comparable to systems known in the art, but its essentially mineral composition makes it much less toxic than known systems of the prior art, much less polluting to the environment and allowing for cost-effective production.
[0084] Furthermore, it has been shown that aqueous slurry-based systems containing a blocked alumina component as the primary binder component and a blocked calcium silicate cement in an aqueous slurry exhibiting an alkaline pH as the secondary binder component can utilize lower water-to-cement ratios compared to state-of-the-art two-component pourable mortars containing a filler-based activator component. Additionally, it has been shown that the long-term strength loss due to conversion characteristic of calcium aluminate cements can be mitigated by blending these two cements to produce stable hydrates of calcium silicate hydrate and portlandite phases.
[0085] Furthermore, the two-component mortar system of the present invention has been shown to contain no harmful substances while maintaining standards for chemical bonding applications, thus encompassing reduced labeling.
Claims
1. A two-component mortar system comprising a cured aqueous phase alumina cement component A and an initiator component B in the aqueous phase for starting the curing process, wherein component A further comprises at least one blocking agent selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid, and phosphonic acid, and water, and component B comprises a blocked calcium silicate cement and water.
2. 2. The two-component mortar system of claim 1, wherein the blocked calcium silicate cement comprises calcium silicate cement and the blocking agent for the calcium silicate cement is selected from the group consisting of monosaccharides, carboxylic acids, gluconic acid, glycolic acid, lignosulfonates, phosphoric and phosphonic acids, their salts and esters, glucose, and mixtures thereof.
3. 3. The two-component mortar system of claim 2, wherein the calcium silicate cement is present in a range of about 10% by weight to about 80% by weight based on the total weight of component B.
4. The two-component mortar system according to claim 2 or 3, wherein the blocking agent for the calcium silicate cement is present in a range of about 0.01 wt% to about 10 wt%, based on the total weight of component B.
5. A two-component mortar system according to any one of claims 2 to 4, wherein the blocking agent is sodium gluconate.
6. The calcium silicate cement is a siliceous clinker phase tricalcium silicate C 3 S, dicalcium silicate C 2 The two-component mortar system according to any one of claims 2 to 5, comprising:
7. The calcium silicate cement is free of aluminate clinker phase and free of lime, most preferably free of aluminate clinker phase and free of lime. 3 The two-component mortar system according to any one of claims 2 to 6, wherein
8. The two-component mortar system according to any one of claims 1 to 7, wherein component A and component B have a shelf life of at least 6 months.
9. The two-component mortar system according to any one of claims 1 to 8, wherein component A and component B are in the form of a slurry or paste.
10. The two-component mortar system according to any one of claims 1 to 9, wherein the pH value of component B is greater than 11.
11. Component B is 45% to 85% by weight of C, free of aluminate clinker phase and free of lime 3 S. and 0.01 to 0.5% by weight of sodium gluconate; 11. The two-component mortar system according to any one of claims 1 to 10, comprising 10% to 35% by weight of water.
12. Use of the two-component mortar system according to any one of claims 1 to 11 for chemical fixing of an anchoring means in a mineral substrate.
13. 13. Use according to claim 12, wherein the fastening means is a metal element, preferably an anchor rod, a threaded anchor rod, a bolt or a steel reinforcement.
14. 14. Use according to claim 12 or 13, wherein the mineral substrate is a structure made of brickwork, concrete, pervious concrete or natural stone.
15. A method for chemically fixing anchoring means in mineral substrates, characterized in that a two-component mortar system is used comprising a cured aqueous phase alumina cement component A and an initiator component B in the aqueous phase for starting the curing process, component A further comprising at least one blocking agent selected from the group consisting of boric acid, phosphoric acid, metaphosphoric acid, phosphorous acid and phosphonic acid, and water, and component B comprising a blocked calcium silicate cement and water, said method comprising: - introducing a borehole into the mineral matrix; - mixing component A with component B to obtain a hardenable alumina cement composition; - inserting the alumina cement composition directly into the borehole; - inserting and adjusting the construction elements to be fixed; - allowing the alumina cement composition to harden and set.
Citation Information
Patent Citations
Expansive quick-setting grout
JP1989108139A
Cement admixture and cement composition
JP1997071444A
Retention system and its use
JP2018534228A
Filler and method for producing filler
JP2019059632A
Two-component mortar fastening materials based on aluminous cement and their use.
JP2019500297A